Quidditch through the ages - Whisp, Kennilworthy; Rowling, J. K. (Arthur A. Levine Books, an imprint of Scholastic Inc. ; in association with WhizzHard Books, 2015)
Quidditch through the Ages is a comprehensive guide to Quidditch and the ultimate resource for anyone interested in the magical world and its most popular sport. Written by Kennillworthy Whisp (aka J.K. Rowling), it is charmingly reproduced as if it were a facsimile of the very copy from the library of the Hogwarts School of Witchraft and Wizardry. This book examines the evolution of quidditch as well as the finer points of modern play as popularized in the muggle world by the wizard, Harry Potter.